Role of Health Care Professionals in Multidisciplinary Pain Treatment Facilities in Canada - Philip Peng; Jennifer N Stinson; Manon Choiniere; Dominique Dion; Howard Intrater; Sandra LeFort; Mary Lynch; May Ong; Saifee Rashiq; Gregg Tkachuk; Yves Veillette; the STOPPAIN Investigators Group (Pain Research and Management)
PURPOSE: To examine the role of health care professionals in multidisciplinary pain treatment facilities (MPTF) for the treatment of chronic pain across Canada.